Influence of leadership empowering behavior on employee innovation behavior: The moderating effect of personal development support - Ye, Pinghao; Liu, Liqiong; Tan, Joseph (Frontiers in Psychology, 2022)
The main purpose of this study is to explore the influence of leadership empowering behavior (personal development support, participative decision making and delegation of authority) and thriving at work (vigor, learning) on employee innovation behavior and analyze the moderating effect of personal development support on participative decision making and innovation behavior. The questionnaire survey method is used to survey Chinese industrial workers, and a total of 290 valid questionnaires are collected. The model is verified using SmartPLS. Results show that the personal development support and participative decision making dimensions of leadership empowering behavior have a significant positive influence on employee innovation behavior. Vigor and learning has a significant positive influence on employee innovation behavior, and personal development support has a significant moderating effect on the relationship between participative decision making and innovative behavior.